One new species of Liara (Orthoptera: Tettigoniidae: Conocephalinae; Agraeciini) from Guangxi - Zhang, Qianwen; Lu, Xiangyi; Bian, Xun (Zootaxa, 2022)
One new species of the genus Liara is described, Liara (Liara) longispina sp. nov. (Chinese name: 长刺雅螽) from Guangxi, China. All the specimens are deposited in Guangxi Normal University. Detailed descriptions and illustrations are provided for the new species.